Education and hope in troubled times [ visions of change for our children's world - Shapiro, H. Svi (Sociocultural, political, and historical studies in education, 2009)
Bringing together a group of the best creative educational thinkers to reflect on the purpose and future of public education, this collection of original essays by leading social and educational